Perkembangan Pradewasa dan Perilaku Parasitisasi Hemiptarsenus varicornis (Girault) (Hymenoptera: Eulophidae) sebagai Ektoprasitoid Larva Liriomyza sativae (Blanchard) (Diptera: Agromyzidae) - I PUTU DARMA WIASA; ANAK AGUNG AYU AGUNG SRI SUNARI; I WAYAN SUPARTHA (Agrotrop : Journal on Agriculture Science, 2018)
Imature Development and Parasitization Behavior of Hemiptarsenus varicornis (Girault) (Hymenoptera: Eulophidae) as a Larval Ectoparasitoid of Liriomyza sativae (Blanchard) (Diptera: Agromyzidae). Liriomyza is one of the important pests that attacking vegetable plants in Indonesia. Parasitoid which is commonly associated with Liriomyza is Hemiptarsenus varicornis. The study was conducted at the Greenhouse of the Faculty of Agriculture, Udayana University and at the Integrated Pest Management Laboratory Faculty of Agriculture, Udayana University, Denpasar. The research starts from February to September 2018. The purpose of this study was to determine the development and parasitization behavior of the pre-adult phase of H. variconis on L. sativae. The development of the parasitoid pre-adult phase was observed in the form of egg, larvae, pupa and imago stages. Observation of pre-adult phase parasitization behavior was carried out by tearing the leaves of plants that had been infested and observed under a binocular microscope. The result indicated that the time required for the development of pre-adult phase H.varicornis was nine days at an average temperature of 28oC, with egg stage (24 hours), larval stage (48 hours) and the pupa stage (120 hours). The parasitization behavior of the immature parasitoid H. varicornis includes three stages, namely the search for hosts, finding the host and receiving the host and directly infusing the host's body fluids, then going away from the host's destroyed body. Host search behavior occurs when new larvae appear, while the process of sucking in body fluids occurs when the instar-1 larvae before the instar-2 and away from the host occur before parasitoid larvae enter the pupa phase.